Psychological Well-Being of Young Lady from a Broken Home Family in Tana Toraja - Nurnaningsih Nurnaningsih; Yuzarion Yuzarion; Purwadi Purwadi; Elli Nur Hayati (Psikostudia : Jurnal Psikologi, 2022)
Teenagers who experience a broken home feel the psychological burden due to the divorce of their parents. There are many cases of broken homes and causes of various problems. Problems can be overcome by fostering psychological well-being. This study aims to reveal the description of psychological well-being and the factors that influence the psychological well-being of adolescent girls from broken homes in Tana Toraja. This study uses a qualitative method with a phenomenological approach. The sampling technique is snowball/chain sampling. The sample is 5 people. The characteristics of the sample are young ladies at 12-23 years, domiciled in Tana Toraja and have been in a broken home for the last 10 years. In-depth interviews and observation methods are data collection methods in this study. The phenomenon obtained is that adolescents experience disappointment with parental figures, need for affection, and open attitude to trusted/closest people, resilience, optimism, and personal growth. Factors that affect the level of psychological well-being are the existence of good social support, age and high motivation to continue to develop their potential. Adolescents from broken homes are associated with negative stigma, but they are able to present themselves positively and better. The results of this study can be implicated in adolescents to become more independent individuals, think rationally, have good relationships with others, be able to develop themselves well, have hope and feel spiritual calm. Remaja yang mengalami broken home merasakan beban psikologis akibat perceraian kedua orang tua. Kasus broken home sangat banyak dan menimbulkan berbagai problematika. Problematika dapat diatasi dengan menumbuhkan kesejahteraan psikologis. Penelitian ini bertujuan untuk mengungkapkan gambaran psychological well-being dan faktor-faktor yang mempengaruhi psychological well-being remaja perempuan dari keluarga broken home di Tana Toraja. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologis. Teknik pengambilan sampelnya adalah snowball/chain sampling. Sampelnya sebanyak 5 orang. Karakteristik sampelnya adalah perempuan, usia 12-23 tahun, berdomisili di Tana Toraja dan berada dalam kondisi broken home selama 10 tahun terakhir. Metode indepth interview dan observasi menjadi metode pengumpulan data dalam penelitian ini. Fenomena yang didapatkan adalah remaja mengalami kekecewaan terhadap figur orang tua, kebutuhan kasih sayang, sikap terbuka kepada orang-orang terpercaya/terdekat, resiliensi, optimis, dan pertumbuhan pribadi. Faktor yang mempengaruhi tingkat psychological well-being adalah adanya dukungan sosial yang baik, faktor usia dan motivasi yang tinggi untuk terus mengembangkan potensinya. Remaja broken home dikaitkan dengan stigma negatif namun kenyataannya ia mampu menampilkan diri yang positif dan lebih baik. Hasil penelitian ini dapat diimplikasikan pada remaja untuk menjadi pribadi yang lebih mandiri, berpikir secara rasional, memiliki hubungan baik dengan orang lain, mampu mengembangkan dirinya dengan baik, memiliki harapan dan merasakan ketenangan spiritual.